24. Continuous EEG-SEP monitoring in acute brain injury: Unstable SEP trend preceding neurological deterioration. Issue 12 (December 2017) - Spalletti, M.; Orzalesi, V.; Carrai, R.; Bucciardini, L.; Cossu, C.; Scarpino, M.; Maestrini, S.; Grippo, A.; Amantini, A.
Abstract : We describe two patients with acute brain injury who underwent continuous EEG-SEP monitoring: an unusual phase of SEPs amplitude instability preluded to cerebral perfusion alterations in one case and to neurological deterioration up to brain death in the other. Raw and quantitative EEG were continuously recorded. Cortical SEPs after stimulation of median nerves were recorded every hour, with amplitude and latency automatically trended. Patient 1 had a subarachnoid hemorrhage due to a left Middle Cerebral Artery (MCA) aneurysm rupture. Increase of intracranial pressure required left decompressive craniectomy. EEG-SEP monitoring was started on day 7, showing a prolonged instability of left SEP: left MCA vasospasm with temporo-parieto-occipital hypoperfusion was demonstrated. After treatment, hypoperfusion and SEP improved. Patient 2 suffered from a right MCA ischemic stroke, treated with systemic thrombolysis. After four days GCS dropped to 5–6, CT showed a severe hemispheric edema requiring a right decompressive craniectomy. Right SEP was absent but left SEP was normal. On day 6 EEG-SEP monitoring was started, showing left SEP instability and gradual deterioration until day 9, when SEP suddenly and permanently disappeared. On day 10 the brain dead of the patient was declared. In acute brain injury, SEP instability during continuous monitoring is an infrequent pattern, with a high risk of neurological deterioration.